The role of probiotics in the correction of the gastrointestinal disorders in children - D. A. Khavkina; P. V. Chukhliaev; T. A. Ruzhentsova (Лечащий Врач, 2021)
The article presents a review of studies devoted to the study of the effectiveness and safety of probiotics in the complex therapy of gastrointestinal disorders in children of various ages. It is noted that the daily use of drugs containing Lactobacillus reuteri protectis in the form of drops dissolved in breast milk, or a mixture, significantly reduces the duration of crying, increases the number and quality of defecation, reduces the number of regurgitations. In addition, L. reuteri protectis has anti-inflammatory, antimicrobial and antiviral effects, participates in cytomucoprotection due to the formation of specific biofilms on the intestinal mucosa, and also produces gammaamino-butyric acid – the main neuroregulator of intestinal motor function. These properties determine the effectiveness of the strain in the treatment and prevention of irritable bowel syndrome, functional abdominal pain, as well as gastritis and peptic ulcer disease associated with Helicobacter pylori. Most studies have noted the important role of the probiotic strain L. reuteri DSM 17938 (protectis) in the correction of functional gastrointestinal dysfunction in children of various ages.